LBA3IMbrave150: Efficacy and safety results from a ph III study evaluating atezolizumab (atezo) + bevacizumab (bev) vs sorafenib (Sor) as first treatment (tx) for patients (pts) with unresectable hepatocellular carcinoma (HCC). (24th November 2019) - Cheng, A-L; Qin, S; Ikeda, M; Galle, P; Ducreux, M; Zhu, A; Kim, T-Y; Kudo, M; Breder, V; Merle, P; Kaseb, A; Li, D; et al.
Abstract: Background: Ph 1b data has shown promising efficacy and safety for atezo + bev in unresectable HCC pts who have not received prior systemic therapy. Here, we report the primary analysis data from the Ph 3 IMbrave150 trial comparing atezo + bev vs sor in this pt population. Methods: IMbrave150 enrolled systemic treatment (tx)-naïve pts with unresectable HCC. Pts were randomised 2:1 to receive either atezo 1200 mg IV q3w + bev 15 mg/kg IV q3w or sor 400 mg BID until unacceptable toxicity or loss of clinical benefit per investigator. Coprimary endpoints were OS and PFS by independent review facility (IRF)-assessed RECIST 1.1. The key secondary endpoints IRF-ORR per RECIST 1.1 and IRF-ORR per HCC mRECIST were also part of the study statistical testing hierarchy. Results: The ITT population included 336 pts randomised to atezo + bev and 165 randomised to sor. Baseline demographics were well balanced between arms. With a median follow up of 8.6 mo, OS HR was 0.58 (95% CI, 0.42, 0.79; P = 0.0006) and PFS HR was 0.59 (95% CI, 0.47, 0.76; P < 0.0001; see table) for atezo + bev vs sor. ORR was 27% vs 12% (P < 0.0001) per IRF RECIST 1.1 and 33% vs 13% (P < 0.0001) per IRF HCC mRECIST for atezo + bev vs sor, respectively. Results were generally consistent across clinical subgroups. Atezo + bev delayed deterioration of quality of life vs sor. Median tx duration was 7.4 mo for atezo, 6.9 for bev and 2.8 for sor. Grade 3-4 AEs occurred in 57% of pts receiving atezo + bev and 55% of pts receiving sor. Grade 5 AEs were seen in 5% and 6% of pts, respectively. Conclusions: IMbrave150 demonstrated statistically significant and clinically meaningful improvement in both OS and PFS for atezo + bev vs sor in pts with unresectable HCC who have not received prior systemic therapy. The safety of atezo + bev is consistent with the known safety profile of each agent, and no new safety signals were identified. Atezo + bev has the potential to be a practice changing tx in HCC. Clinical trial identification: NCT03434379. Editorial acknowledgement: Medical writing assistance for this abstract was provided by Jessica Bessler, PhD, of Health Interactions, Ltd. and funded by F. Hoffmann-La Roche, Ltd. Legal entity responsible for the study: F. Hoffmann-La Roche, Ltd. Funding: F. Hoffmann-La Roche, Ltd. Disclosure: A-L. Cheng: Advisory / Consultancy: Bayer Schering Pharma; Advisory / Consultancy: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Eisai; Advisory / Consultancy: Merck Serono; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Ono Pharmaceutical; Advisory / Consultancy: Exelixis; Advisory / Consultancy: Nucleix Ltd.; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche/Genentech; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: IQVIA; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bayer Yakuhin, Ltd; Speaker Bureau / Expert testimony: Amgen Taiwan; Honoraria (self): Bayer; Honoraria (self): Merck Sharp Dohme; Honoraria (self): Merck Serono. M. Ikeda: Honoraria (self): Abbott Japan; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bayer Yakuhin; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self): Bristol-Myers Squibb Japan; Honoraria (self), Research grant / Funding (institution): Chugai Pharma; Honoraria (self), Research grant / Funding (institution): Daiichi Sankyo; Honoraria (self), Honoraria (institution), Research grant / Funding (institution): Eisai; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Lilly Japan; Honoraria (self): Nippon Kayaku; Honoraria (self): Novartis; Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical; Advisory / Consultancy, Research grant / Funding (institution): Kyowa Hakko Kirin; Advisory / Consultancy, Research grant / Funding (institution): NanoCarrier; Research grant / Funding (self): ASLAN Pharmaceuticals; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Baxter; Research grant / Funding (self): Boehringer Ingelheim; Research grant / Funding (self): Kowa; Research grant / Funding (self): Merck Serono; Research grant / Funding (self): Ono Pharmaceutical, Yakult, Zeria Pharmaceutical. P.R. Galle: Honoraria (self), Research grant / Funding (institution): Bayer; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): MSD; Honoraria (self): AstraZeneca; Honoraria (self): SIRTEX; Honoraria (self): Merck; Honoraria (self): Lilly; Honoraria (self): Blueprint; Honoraria (self): AdaptImmune; Honoraria (self): Eisai; Honoraria (self): Roche; Honoraria (self): Ipsen. M.P. Ducreux: Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Servier; Advisory / Consultancy: Amgen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Celgene; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Ipsen; Advisory / Consultancy, Travel / Accommodation / Expenses: Merck Serono; Advisory / Consultancy: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony: Bayer; Speaker Bureau / Expert testimony: Merck KGaA; Research grant / Funding (self): Pfizer; Spouse / Financial dependant: Sandoz. A.X. Zhu: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Eisai; Advisory / Consultancy: Exelixis; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy: Roche/Genentech. M. Kudo: Honoraria (self), Research grant / Funding (institution): AbbVie; Honoraria (self), Advisory / Consultancy: Bayer; Honoraria (self), Research grant / Funding (institution): Bristol-Myers Squibb Japan; Honoraria (self): EA Pharma; Honoraria (self), Advisory / Consultancy: Eisai; Honoraria (self): Gilead Sciences; Honoraria (self): Merck Serono; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self): Novartis; Honoraria (self): Pfizer; Honoraria (self), Research grant / Funding (institution): Taiho Pharmaceutical; Advisory / Consultancy: Bristol-Myers Squibb; Research grant / Funding (institution): Astellas Pharma; Research grant / Funding (institution): Chugai Pharma; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Otsuka. V. Breder: Honoraria (self), Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bayer; Honoraria (self), Advisory / Consultancy: BioCad; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy: Eisai; Honoraria (self), Advisory / Consultancy: MSD Oncology; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Honoraria (self), Travel / Accommodation / Expenses: Takeda. P. Merle: Research grant / Funding (self): ONXEO; Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Travel / Accommodation / Expenses: Ipsen; Advisory / Consultancy: Eisai; Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy, Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: Bristol-Myers Squibb. A. Kaseb: Shareholder / Stockholder / Stock options: Gilead Sciences; Honoraria (self), Advisory / Consultancy: Bayer Health; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Exelixis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Merck; Research grant / Funding (self): Genentech; Research grant / Funding (self), Travel / Accommodation / Expenses: Bayer/Onyx. D. Li: Advisory / Consultancy: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Exelixis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Ipsen; Honoraria (institution), Speaker Bureau / Expert testimony: Lexicon; Advisory / Consultancy: Novartis; Speaker Bureau / Expert testimony: Advanced Accelerator Applications. W. Verret: Full / Part-time employment: Genentech. Z.D. Xu: Full / Part-time employment: Roche. S. Hernandez: Shareholder / Stockholder / Stock options, Full / Part-time employment: Genentech. J. Liu: Full / Part-time employment: Roche. C. Huang: Full / Part-time employment: Roche. S. Mulla: Full / Part-time employment: Roche. R. Finn: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Bayer; Advisory / Consultancy: BristolMyersSquibb; Advisory / Consultancy: Eisai; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Merck; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche/Genentech; Speaker Bureau / Expert testimony: Novartis.